Targeting Siglec-E facilitates tumor vaccine-induced antitumor immunity in renal carcinoma - Yuchen Zhang; Junnian Zheng; Li Sun; Guangya Zhao; Yingxiang Shao; Bowen Lu; Jiage Ding; Yanyan Zheng; Renjin Chen; Dafei Chai; Jiawei Wang; Zichun Zhang; et al. (Journal for ImmunoTherapy of Cancer)
Background Siglec-E is an immune checkpoint inhibitory molecule. Expression of Siglec-E on the immune cells has been shown to promote tumor regression. This study aimed to develop an adenovirus (Ad) vaccine targeting Siglec-E and carbonic anhydrase IX (CAIX) (Ad-Siglec-E/CAIX) and to evaluate its potential antitumor effects in several preclinical renal cancer models.Methods Ad vaccines encoding Siglec-E or CAIX were developed and evaluated for their therapeutic potential in mouse subcutaneous, lung metastatic, and orthotopic tumor models. The expression of Ad-Siglec-E/CAIX was confirmed via PCR and flow cytometry. Immune responses induced by Ad-Siglec-E/CAIX were assessed in vitro and in vivo using flow cytometry, immunohistochemistry, ELISA, histological analysis, cell proliferation, enzyme-linked immunosorbent spot, cytotoxic T lymphocytes (CTL) killing, and cell depletion assays.Results Ad-Siglec-E/CAIX vaccine induced the increase of tumor-infiltrated immune cells, and significantly suppressed the subcutaneous tumor growth of renal carcinoma. Immunization with Ad-Siglec-E/CAIX promoted the induction and maturation of CD11c+ dendritic cells and their subsets, which in turn enhanced tumor-specific CD8+ T cell immune responses, as evidenced by increased CD8+ T cell proliferation and CTL activity. Importantly, the deletion of CD8+ T cells in vivo abolished the antitumor effect of the Ad-Siglec-E/CAIX vaccine, highlighting the essential role of functional CD8+ T cell responses. The potent therapeutic efficacy of the Ad-Siglec-E/CAIX vaccine was also observed in lung metastasis and orthotopic tumor models through tumor-specific CD8+ T cell immune responses.Conclusions Our results indicate that targeting Siglec-E enhances the therapeutic efficacy of Ad-CAIX against renal carcinoma, providing a promising therapeutic option for solid tumors.